Investigating the normal dimensions and sizes of human eye orbit by MRI in Labafinejad Hospital patients in 2016 in Tehran - Aghajanpour, Fakhroddin; Soltani, Reza; Nourozian, Mohsen; Fadaei, Fatemeh; Abbaszadeh, Hojjat-Allah; Mastery Farahani, Reza (Student Research in Translational Medicine, 2019)
Background: Anthropometry is one of the principal researches in. The eye orbit is involved in most cranial abnormalities. Concerning the lack of adequate information in Iranian populations and the effect of factors including gender, age, and geographical region, the aim of this study was to investigate the normal dimensions and sizes of human eye orbit through MRI. Materials and Methods: This was a descriptive, analytical, and prospective study which was performed on 120 patients referring to the MRI center of Labafinejad and Torfeh hospitals. In fact, 20 patients were excluded due to eye-associated disorders. The longitudinal and transversal axes, as well as the eye orbit volume were measured, and the age, gender, and the sidedness of eye were reported and evaluated. Results: The mean age was 38, and the eye orbit volume, longitudinal axis, and transversal axes were measured as 5593 mm3, 22 mm, and 21.9 mm, respectively. The minimum average measured value was related to the distance between the posterior edge of the frontal processes of the upper jaw bones (21 mm in females and 23 mm in males), while the maximum average was measured across the posterior poles of the two eye orbits (26 mm in females and 29 mm in males) (P<0.4). Conclusion: The data suggestd that the longitudinal and transversal axes, as well as the volume of right and left eyes are larger in men than in women. The difference in the eye orbit volume of men, as compared to women can be attributed to a large body mass in men.